ANALISIS CULTURALLY RESPONSIVE TEACHING (CRT) PADA MATERI PENGUKURAN JARAK DI KELAS 2 SD - Dini Firda Novita Putri; Aryo Andri Nugroho (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Learning approach is one of thing that must be considered before conducting a learning activity. One of learning approach that can be implemented is CRT (Culturally Responsive Teaching). This research aimed to find the result of analyzing CRT in mathemathics subject especially in topic of distance measurement. The researcher decided to use descriptive qualitative analysis as research method that focus on CRT in learning mathemathics subject especially in topic of distance masurement at Grade 2 in one of Elementary School in Semarang and using interview and observation as technique in collecting data. Based on the results of the analysis, it was found that the implementation of CRT in the mathemathics subject focuse on distance measurement was in accordance with the 5 characteristics of CRT according to Rahmawati and steps for its descriptive implementation according to El-Fadilah. Keywords: Learning Approach, CRT (Culturally Responsive Teaching), Mathemathics